2019
DOI: 10.2147/jpr.s216184
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Effect Of The Use Of Pre-Emptive Oral Pregabalin On The Postoperative Spinal Analgesia In Patients Presented For Orthopedic Surgeries: Randomized Controlled Trial</p>

Abstract: BackgroundPreoperative oral pregabalin could improve postoperative analgesia and prevent chronic pain development. The aim of this study is to evaluate the effect of oral pregabalin on the duration and quality of postoperative analgesia in spinal anesthesia.MethodsSixty adult patients presented for internal fixation of femoral fracture under spinal anesthesia were included in the study. They were randomly distributed to a placebo group and a pregabalin group receiving 150 mg pregabalin capsules 1 hr before sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Trials were defined as moderate quality if they did not meet the above criteria. Sixteen trials were graded as high quality [ 12 14 , 16 – 18 , 20 – 23 , 25 , 27 , 28 , 30 32 ], and five trials were graded as moderate quality [ 15 , 19 , 24 , 26 , 29 ]. The details of the quality assessment are displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Trials were defined as moderate quality if they did not meet the above criteria. Sixteen trials were graded as high quality [ 12 14 , 16 – 18 , 20 – 23 , 25 , 27 , 28 , 30 32 ], and five trials were graded as moderate quality [ 15 , 19 , 24 , 26 , 29 ]. The details of the quality assessment are displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown the analgesic efficacy of using pregabalin in perioperative setting. 21,22 However, the role of pregabalin in cancer-induced pain is controversial. In a study of patients with cancer-induced bone pain, pregabalin combining with palliative radiotherapy did not show additional benefit compared to patients receiving radiotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the analgesic efficacy of using pregabalin in perioperative setting 21,22 . However, the role of pregabalin in cancer‐induced pain is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted to evaluate the effect of oral pregabalin on the duration and quality of postoperative analgesia in spinal anesthesia, it was shown that oral pregabalin extended the duration of postoperative analgesia and reduced morphine intake. Moreover, it improved sleep quality during the first postoperative night (43). In another study aimed at investigating the effect of prophylactic use of oral pregabalin-acetaminophen-naproxen on pain control and morphine usage in patients who had undertaken laparotomy, patients in the PAN group (pregabalin 150 mg, acetaminophen 1 g, and naproxen 250 mg) experienced lower pain and the morphine use was also significantly lower than the control group (44).…”
Section: Meanmentioning
confidence: 99%